Paradoks Globalisasi Multidimensi: Analisis Bukti Empiris dari Pertumbuhan Ekonomi di ASEAN - Restu A Suryaman; Sardoraja Sardoraja; Anwar Maulana; M Iqbal Baihaqi (PPJP ULM, 2026)
This study examines the impact of multidimensional globalization on economic growth in ASEAN countries over the period 2019–2024. Using the KOF Globalisation Index, globalization is decomposed into economic, social, and political dimensions to capture its heterogeneous effects. Panel data estimation is conducted using the Fixed Effect Model (FEM), with System Generalized Method of Moments (System GMM) employed as a robustness check to address potential endogeneity. The results reveal that economic globalization and foreign direct investment have a positive and significant effect on economic growth, indicating the important role of trade integration and capital inflows in enhancing economic performance. In contrast, political globalization shows a negative and significant effect, supporting the existence of a globalization paradox, where deeper political integration may reduce domestic policy flexibility and hinder growth. Social globalization and labour force are not statistically significant. The System GMM results confirm the robustness and consistency of the main findings. These results highlight that globalization has asymmetric effects, implying that ASEAN countries need to adopt a selective and strategic globalization approach to promote sustainable economic growth.